A case report of sofosbuvir and daclatasvirto treat a patient with acute hepatitis C virus genotype 2 monoinfection. Issue 15 (April 2018) - Li, Chen; Hu, JinHua
Abstract: Rationale: Direct-acting antivirals (DAAs) are the first-line treatment for patients with chronic hepatitis C virus (HCV) infection. However, its effects on patients with acute HCV infection are poorly understood, and the data for treatment of DAAs for genotype 2 acute monoinfection patients with HCV are lacking. Patient concerns: In this case report, a 26 year-old Chinese female acquired a tattoo and developed fatigue, nausea, and anorexia. Laboratory tests showed abnormal liver function. Diagnoses: Five months after the patient acquired a tattoo, laboratory tests showed anti-HCV antibody titers were 26.0 s/co, HCV RNA was 5.74×10 5  IU/mL, and HCV genotype was 2a. The patient was diagnosed with acute hepatitis C (AHC). Interventions: HCV RNA did not have spontaneous clearance 12 weeks after the infection of the patient. The patient received sofosbuvir (SOF) and daclatasvir (DCV) combination treatment for 12 weeks. Outcomes: Laboratory tests showed HCV RNA was undetectable at weeks 4, and anti-HCV antibody was in seroconversion at weeks 12 during treatment. The patient achieved a sustained virological response 36 weeks after the end of treatment. Lessons: Patients with acute HCV genotype 2 monoinfection would benefit from antiviral treatment with SOF and DCV.